The Responsive Law Paradigm in the Enforcement of Election Criminal Offenses: Reorientation of Bawaslu's Authority as an Independent Investigator - Muhammad Wahdini; Muhammad Noor Shaleh; Ranti Suminar Endah; Ahmad Baihaki (Equality Before The Law, 2026)
Enforcement of election-related criminal offenses in Indonesia continues to face various institutional obstacles due to the limited authority of the Election Supervisory Body (Bawaslu), which functions only as a supervisor and reporter, while investigative authority rests with the Police through the Integrated Law Enforcement Center (Gakkumdu). Data from the National Legal Development Agency shows that in the 2019 General Election, only 345 of 2,798 alleged election criminal offenses discussed at the Gakkumdu Center were declared to meet the elements of a criminal offense, indicating that the effectiveness of election criminal law enforcement remains low. This study aims to analyze the philosophical, juridical, and sociological foundations for strengthening Bawaslu's investigative authority through the perspective of the Responsive Law theory of Philippe Nonet and Philip Selznick. This research is normative legal research employing statutory, conceptual, and case approaches, supported by secondary empirical data in the form of official reports from Bawaslu and the National Legal Development Agency, as well as scholarly literature to reinforce the normative analysis. The results show that the current institutional design for enforcing election criminal offenses still reflects the character of autonomous law, oriented toward formal procedure, and thus does not yet fully guarantee substantive electoral justice. From the perspective of Responsive Law, effective law enforcement requires institutions that are adaptive, independent, and oriented toward protecting citizens' political rights. Therefore, reconstructing Bawaslu's investigative authority is regarded as a viable legal policy alternative worth considering through amendments to statutory regulations, while still upholding the principle of checks and balances within the criminal justice system, in order to strengthen electoral integrity and the quality of democracy in Indonesia.